Analysing cycles in stock price indices using fast fourier transform. - Chong, Audrey Yu Shan. (2008)
In our research, we explore, using Fast Fourier Transform to identify the presence of cycles in stock price indices. In addition, we analyse the stability of these prices over time and hence the feasibility of this technique in the prediction of stock price indices.